2023
DOI: 10.1101/2023.01.23.23284899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world effectiveness of Azvudine in hospitalized patients with COVID-19: a retrospective cohort study

Abstract: Current guidelines prioritize the use of the Azvudine in coronavirus disease 2019 (COVID-19) patients. However, the clinical effectiveness of Azvudine in real-world studies was lacking, despite the clinical trials showed shorter time of nucleic acid negative conversion. To evaluate the clinical effectiveness following Azvudine treatment in hospitalized COVID-19 patients, we identified 1505 hospitalized COVID-19 patients during the study period, with a follow-up of up to 29 days. After exclusions and propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…These results were consistent with the interim analysis of an unpublished phase 3 multi-centre randomised clinical study 6 and our previous real-world study. 15 Interestingly, we found that Azvudine had a stronger protective effect on severe patients with COVID-19 who were not recommended for the use of Paxlovid and molnupiravir. 20 , 21 A previous single arm clinical trial reported that all patients with severe COVID-19 were recovered after oral Azvudine.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These results were consistent with the interim analysis of an unpublished phase 3 multi-centre randomised clinical study 6 and our previous real-world study. 15 Interestingly, we found that Azvudine had a stronger protective effect on severe patients with COVID-19 who were not recommended for the use of Paxlovid and molnupiravir. 20 , 21 A previous single arm clinical trial reported that all patients with severe COVID-19 were recovered after oral Azvudine.…”
Section: Discussionmentioning
confidence: 71%
“… 6 Our previous study also showed that Azvudine helped to improve the prognosis in general patients with COVID-19. 15 However, whether Azvudine reduces the adverse clinical outcomes in hospitalised patients with COVID-19 with pre-existing comorbidities remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Nevertheless, the real-world effectiveness of Azvudine versus nirmatrelvir-ritonavir is still lacking, despite clinical studies showing their effectiveness compared with matched controls. [9][10][11]13,14 In this retrospective cohort study, a total of 2118 hospitalized patients with COVID-19 were identified during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Current guidelines prioritize the use of nirmatrelvir–ritonavir and Azvudine in COVID‐19 patients 2–4 . Nevertheless, the real‐world effectiveness of Azvudine versus nirmatrelvir–ritonavir is still lacking, despite clinical studies showing their effectiveness compared with matched controls 9–11,13,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation